2019
DOI: 10.1152/physiol.00008.2019
|View full text |Cite
|
Sign up to set email alerts
|

We Are Upright-Walking Cats: Human Limbs as Sensory Antennae During Locomotion

Abstract: Humans and cats share many characteristics pertaining to the neural control of locomotion, which has enabled the comprehensive study of cutaneous feedback during locomotion. Feedback from discrete skin regions on both surfaces of the human foot has revealed that neuromechanical responses are highly topographically organized and contribute to “sensory guidance” of our limbs during locomotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 98 publications
0
20
0
Order By: Relevance
“…Somatosensory feedback from the lower limb, and in particular from the foot sole, plays an important role in controlling balance, posture, and gait (Inglis et al 2002;Pearcey and Zehr 2019). The foot sole is covered with glabrous skin and innervated by the same four classes of tactile afferents as the hand (SAI, SAII, FAI, FAII).…”
Section: Glabrous Skin Of the Foot Solementioning
confidence: 99%
“…Somatosensory feedback from the lower limb, and in particular from the foot sole, plays an important role in controlling balance, posture, and gait (Inglis et al 2002;Pearcey and Zehr 2019). The foot sole is covered with glabrous skin and innervated by the same four classes of tactile afferents as the hand (SAI, SAII, FAI, FAII).…”
Section: Glabrous Skin Of the Foot Solementioning
confidence: 99%
“…Even though the importance of forelimb/hindlimb coupling may be amplified in quadrupeds, there is circumstantial evidence that suggests this phenomenon also exists in bipedal animals. Coupling of bipedal arm and leg movements has been observed in upright walking (Dietz, 2002; Zehr et al, 2009, 2016; Frigon, 2017; Pearcey and Zehr, 2019), swimming (Wannier et al, 2001), and crawling (MacLellan et al, 2013) in humans, mirroring the expected behavior of paired oscillators observed in quadrupedal locomotion.…”
Section: Propriospinal Interneurons Coordinate Forelimb and Hindlimb mentioning
confidence: 65%
“…A most remarkable synthesis of the effects of cutaneous input from discrete regions of the foot during walking can be found in Pearcey and Zehr. 64 One may note that locomotion produces a continuous spatiotemporal change in the plantar pressures (and from foot dorsum when wearing shoes 65 ), thereby continuously varying the foot areas from which skin receptors are activated. 65,66 For instance, remarkable changes in the plantar pressure occur between straight and curved walking, 67 potentially informing the brain on how to adapt the body motion to the complex condition of steering while walking.…”
Section: Cutaneous Input and Gaitmentioning
confidence: 99%